PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN HANDPHONE OPPO SMARTPHONE (Studi pada konsumen CV. Surya Sakti Persada Sinarmas Selluler Cabang Matahari Plaza Simpang Lima Semarang) - Rina Widiastuti, 14.05.51.0015; Soliha, Euis (Students' Journal of Economic and Management, 2019)
The purpose of this study was to determine the effect of product quality, price perception, and promotion on the purchasing decision process of the Oppo Smartphone mobile phone (Study on CV. Surya Sakti Persada Sinarmas Selluler Matahari Simpang Lima Semarang branch). The study used the questionnaire method as data collection. The population in this study were consumers of the Oppo Smartphone on CV. Surya Sakti Persada Sinarmas Selluler Matahari branch Simpang Lima Semarang. The sampling technique in this study used purposive sampling. Data analysis using multiple linear regression. The results showed that product quality had a positive and significant effect on the process of buying Oppo Smartphone. Furthermore, the Price Perception has a positive and significant effect on the process of purchasing Oppo Smartphone and Promotional Mobile phones with a positive and significant effect on the process of buying Oppo Smartphone.